Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae) - Sun, Changhai (Zootaxa, 2016)
Two new species of the Rhyacophila angulata Species Group are diagnosed, described and illustrated. Rhyacophila asymmetra n. sp. from Guang-dong Province can be separated from other members of the group by asymmetrical parameres and by the apicodorsal lobe abruptly narrowed in the apical one-third. Rhyacophila dentalis n. sp. from Guang-xi resembles R. longistyla in male genitalia, but can be diagnosed by the sinuate anterior margin of segment IX, by the absence of apicolateral teeth on the apicodorsal lobe of segment IX, and by the presence of a blunt tooth on the upper margin of the basal segment of each inferior appendage. New collection data are added for R. longistyla, extending its distribution southward to Guang-dong and Guang-xi Provinces. Rhyacophila tetraphylla has been transferred from the R. naviculata Species Group to the R. angulata Group with new collection data. A checklist of the species group is provided, and its distribution is discussed.